Multiple Inhibition of Platelet Activation by Aurintricarboxylic Acid Prevents Vascular Stenosis after Endothelial Injury in Hamster Carotid Artery - Matsuno, Hiroyuki; Kozawa, Osamu; Niwa, Masayuki; Tanabe, Kumiko; Ichimaru, Katsuhiro; Takiguchi, Yoshiharu; Yokota, Masayuki; Hayashi, Hideharu; Uematsu, Toshihiko (Thrombosis and Haemostasis, 1998)
Activated platelets are instrumental in restenosis due to their role in thrombus formation. Aurintricarboxylic acid (ATA) has been reported to prevent platelet activation by inhibiting von Willebrand factor binding to platelet glycoprotein (GP) Ib. We investigated the effects of ATA in vitro and in vivo in hamsters. ATA inhibited the in vitro platelet aggregation induced by ADP, botrocetin and thrombin, but not by collagen. The IC50 values during the ex vivo platelet aggregation by ADP, botrocetin and thrombin were 8.2 ± 1.8 μM, 0.9 ± 0.4 μg/ml and 2.4 ± 0.8 unit/ml, respectively. The platelet retention time to collagen-coated beads of hamster blood samples was inhibited by ATA (0.1, 0.3 and 1.0 mg/kg per hour) in a dose-dependent manner. Continuous administration of ATA (0, 0.1, 0.3, 1.0, 3.0 and 10.0 mg/kg per h) via an infusion pump produced dose-dependent antithrombotic effects: the time to occlude the carotid artery after vascular injury with a modified catheter was prolonged. Only when infused at doses of 3.0 and 10.0 mg/kg per hour, bleeding times were significantly prolonged. The continuous treatment with ATA (1.0 mg/kg per h) using a 2ML1 Alzet infusion pump for 2 weeks, resulted in a decrease in neointimal area by 22.2 ± 6.8% when measured 2 weeks after injury induction. DNA synthesis using DDT1MF2 hamster SMCs was decreased by ATA in a dose-dependent manner. ATA reduced the number of platelets adhering on the injured area, as detected by electron microscopy. These results indicated that treatment with ATA inhibited platelet adhesion but also SMC proliferation. These observations may explain the effect of ATA on neointima formation.